A Preliminary Comparative Study of Young's Modulus Versus Shear Modulus in the Diagnosis of Breast Cancer. Issue 1 (March 2019) - Wu, Huaiyu; Liang, Weiyu; Jiao, Yang; Song, Hong; Peng, Quanzhou; Luo, Hui; Zhang, Yuanji; Xu, Jinfeng; Dong, Fajin
Abstract : Purpose: The purpose of this study was to compare the diagnostic value of Young's modulus ( E ) and shear modulus ( G ) in the differential diagnosis of benign and malignant breast masses using sound touch elastography (STE) and to explore the relationship between G and E in breast lesions. Methods: A total of 96 consecutive women with 110 pathologically confirmed breast masses were included. All masses were detected by conventional and STE ultrasound. E mean, E max, E min, E SD, G mean, G max, G min, and G SD were determined and evaluated for evidence of significant differences between benign and malignant breast masses. Receiver operator characteristics were used to compare the diagnostic efficacy of E and G and to determine the G cutoff value that would aid in the differential diagnosis of breast cancer. Results: E mean, E max, E SD, G mean, G max, and G SD in cases of malignant breast masses were significantly higher than those in cases of benign masses ( P < 0.05). There was no significant difference between E min and G min ( P = 0.565). In applying the E mean, E max, E SD, G mean, G max, and G SD to the receiver operator characteristics: (1) the area under the curve (AUC) of G mean and G max is greater than the AUC of E mean and E max, and the AUC of E SD is equal to the AUC of G SD . (2) The sensitivity and specificity were highest when the G mean was 10.14 kPa. They were 84.1% and 80.3% respectively. (3) The sensitivity and specificity were highest when the G max was 52.20 kPa. They were 88.6% and 87.9% respectively. Conclusions: These preliminary results of STE evaluation of breast masses suggest that the diagnostic value of G is greater than E . Furthermore, STE is a valuable tool in the differential diagnosis of breast lesions.